Упростите выражения 1.-2a-2(-а+7)+14 2. 3(-2x-4)+2(3x+8)+2x 3. -(x-y)+(-x+y) 4. -6a+3(2-2a) 5. 4(0,2x-7)-5(0,3x+6) 6. -0,3(5x-7)-3(0,2+3,2x) 7. 4(3-x)-11+7(2x-5) 8. -3(2x+4y)+2(16x-28y) 9. 9,6-(2,6-y)+3(1,2+0,8y) 10. -(-8x+7)+4...
Упростите выражения
1.-2a-2(-а+7)+14
2. 3(-2x-4)+2(3x+8)+2x
3. -(x-y)+(-x+y)
4. -6a+3(2-2a)
5. 4(0,2x-7)-5(0,3x+6)
6. -0,3(5x-7)-3(0,2+3,2x)
7. 4(3-x)-11+7(2x-5)
8. -3(2x+4y)+2(16x-28y)
9. 9,6-(2,6-y)+3(1,2+0,8y)
10. -(-8x+7)+4(-2x-9)
Ответ(ы) на вопрос:
1) -2a-2(-a+7)+14= -2a+2a-14+14=0
2)3(-2x-4)+2(3x+8)+2x=-6x-12+6x+16+2x=2x+4
3) -(x-y)+(-x+y)=-x+y+x+y=2y
4) -6a+3(2-2a)=-6a+6-6a=6-12a
5) 4(0,2x-7)-5(0,3x+6)=0,8x-28-1,5x-30=-0.7x-58
6)-0,3(5x-7)-3(0,2+3,2x)=-1.5x+2,1-0,6-9,6x=1.5-11.1x
7)4(3-x)-11+7(2x-5)=12-4x-11+14x-35=10x-34
8)-3(2x+4y)+2(16x-28y)=-6x-12y+32x-56y=26x-68y
9)9,6-(2,6-y)+3(1,2+0,8y)=9,6-2,6+y+3,6+2,4y=3,4y+10,6
10)-(-8x+7)+4(-2x-9)=8x-7-8x-9=-16
Не нашли ответ?
Похожие вопросы